Anterior open bite treatment with bonded spurs associated with build-ups versus conventional bonded spurs: a randomized clinical trial - Del Castillo, Arón Aliaga (2020)
Introduction: The aim of this 2-arm parallel randomized clinical trial was to compare the dentoskeletal and dental arches changes after anterior open bite early treatment with bonded spurs associated with posterior build-ups versus conventional bonded spurs. Methods: Patients between 7 and 11 years old with anterior open bite were prospectively and randomly allocated to two groups. The experimental group consisted of patients treated with bonded spurs associated with posterior build-ups. The comparison group comprised patients treated with conventional bonded spurs. Lateral headfilms and digital dental models were obtained at pretreatment (T1) and after 12 months of treatment (T2). The primary outcomes were the change in overbite, gonial and mandibular plane angles, and molars vertical development. Randomization was performed using the web site www.randomization.com. Blinding was applicable for outcome variables assessment only. Intergroup comparisons were performed with t tests or Mann-Whitney U tests (P<0.05). Results: The experimental group included 24 patients (17 female; 7 male, mean age 8.22 ± 1.06) and the comparison group included 25 patients (14 female; 11 male, mean age 8.30 ± 0.99). After 12 months, all patients showed improvements. The groups showed similar increases of the overbite and similar dentoskeletal and dental arches changes. The experimental group showed statistically significant smaller vertical development of the maxillary first molar than the comparison group. The groups showed statistically significant differences for the intermolar distances. The maxillary intermolar distance decreased in the experimental group and increased in the comparison group, while the mandibular distance increased in the experimental group and decreased in the comparison group. Conclusions: Similar overbite increases, dentoskeletal and dental arches changes were observed in both groups after 12 months of treatment. Although bonded spurs associated with build-ups showed significant smaller vertical development of the maxillary molars, it did not produce greater counter-clockwise rotation of the mandible than conventional bonded spurs. A slight decrease in the maxillary intermolar distance and a slight increase in the mandibular intermolar distance could be expected with bonded spurs associated with posterior build-ups, while the opposite behavior could be expected when conventional bonded spurs are used.